Revitalizing Pancasila as Living Philosophy: Socratic-Based Classroom Experimentation to Foster Critical Thinking Skills - Andri Fransiskus Gultom (Paidea : Jurnal Pendidikan dan Pembelajaran Indonesia, 2025)
Traditional Pancasila education often suffers from dogmatic rote learning, distancing the state ideology from students' lived realities. This research aims to transform Pancasila from a static doctrine into a "Living Philosophy" through Socratic-based classroom experimentation. Using a qualitative case study approach, this research engaged 80 university students in dialectical sessions focused on ethical-political dilemmas. The findings reveal that Socratic inquiry fosters critical thinking by dismantling ideological passivity. The study identifies a significant shift toward "Civic-Maieutics," a new pedagogical state where students function as "intellectual midwives" for constitutional values. This process facilitates "Pancasila-Aporia," a creative cognitive tension that forces learners to bridge the gap between abstract principles and complex social realities, rather than merely memorizing them. This research introduces the concept of "Ethico-Dialectical Citizenship," a framework where critical questioning becomes a primary civic virtue. This study contributes to the global discourse on transformative pedagogy by demonstrating how classical philosophical methods can modernize national ideological education in post-truth democratic societies.